Fetal surgery: Current situation - Huamán Guerrero, Moisés (2018)
Fetal surgery, or better called maternal-fetal, because drugs and surgical techniques are administered to the fetus through the mother, therefore, share risks, began more than 40 years ago. In 2016, on the subject of a symposium on the relevance of fetal medicine in Peru, published in this journal, we affirmed: "These advances make up a new multidisciplinary medical specialty, which considers the fetus as an individual patient and in the relationship with its mother. , establishing prophylactic treatments, direct medical therapy or through the mother, interventions guided by ultrasound, open and fetoscopic surgeries, with advantages to conventional treatments. This reality obliges us to review ethical and legal aspects related to the unborn, to changes both in the organization of health services, and in the pre and postgraduate curricula of new professionals ". We added: "Currently, in our country, the application of these advances is in the incipient stage. At the decision levels of health policies there is ignorance and disinterest in the subject despite being a priority. However, academic and scientific institutions insist on the need to create a formal organization within the health system that guarantees quality Fetal Medicine "(1).